The beekeeper [videorecording (DVD)] - Wimmer, Kurt, 1964-; Statham, Jason, 1967-; Raver-Lampman, Emmy; Hutcherson, Josh; Naderi, Bobby, 1984-; Driver, Minnie; Witts, David, 1991-; Epp, Michael, 1983-; James, Taylor, 1980-; Redgrave, Jemma; Cilenti, Enzo, 1974-; Rashad, Phylicia, 1948-; et al. (MGM, 2024)
One man's brutal campaign for vengeance takes on national dangers after he is revealed to be a former operative of a powerful and cover organization known as "Beekeepers."